Apomorphine for the treatment of refractory motor fluctuations in late stage Parkinson's disease : an old drug revisited - Pérez Lloret, Santiago (2013)
Fil: Pérez Lloret, Santiago. Hospital Universitario de Toulouse. Departamento de Farmacología Clínica; Francia